PENGARUH PEMAHAMAN PERPAJAKAN, KEADILAN DAN TEKNOLOGI PERPAJAKAN TERHADAP PERILAKU PENGGELAPAN PAJAK: Studi Empiris Pada Wajib Pajak Orang Pribadi Terdaftar di KPP Pratama Serpong - Asri Novia Dewi; Wiwit Irawati (Gapenas Publisher, 2022)
This study aims to determine whether there is an influence on understanding of taxation, justice and taxation technology on tax evasion behavior at the Serpong Pratama Tax Service Office. The type of data used in this research is the type of quantitative data with primary data sources. The population in this study are individual taxpayers registered at KPP Pratama Serpong. This study uses the convenience sampling method, while the data collection technique is by distributing questionnaires to 100 respondents who have been calculated using the slovin formula. And data processing using SPSS 25. The data analysis technique used is multiple linear regression analysis. The results of this study indicate that (1) Partially, understanding of taxation has an effect on tax evasion behavior, (2) partially, justice has no effect on tax evasion behavior, (3) partially, tax technology has an effect on tax evasion behavior, (4) Simultaneously, understanding of taxation, justice and taxation technology affect tax evasion behavior